Applied Numerical Methods with Python for Engineers and Scientists - Chapra, Steven C.; Clough, David E. (McGrawHill Education, 2022)
Applied Numerical Methods with Python, 1st Edition is written for students who want to learn and apply numerical methods in order to solve problems in engineering and science. As such, the methods are motivated by problems rather than by mathematics. Sufficient theory is provided so students come away with insight into the techniques and their shortcomings. If you have ever used Applied Numerical Methods for MATLAB, you'll find transitioning to this Python program seamless!